Magnetic Metal-Organic Frameworks for Efficient Carbon Dioxide Capture and Remote Trigger Release - Li, Haiqing (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.